2021
DOI: 10.3390/su13179635
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and Restoration of Roadside Tree Alleys in Line with Sustainable Development Principles—Mission (Im)possible?

Abstract: The main challenge in the efforts to protect roadside tree alleys is to achieve a balance between the local development and the conservation of biodiversity. The problem of aging and disappearing roadside tree alleys was analyzed based on a critical review of the literature, various types of reports related to this topic and the provisions of international and Polish acts of law on biodiversity conservation and landscape protection. The following research hypotheses were formulated: 1. The preservation and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Most roadside trees consist of broadleaved trees which were usually the same species, similar in tree age (i.e., tree height and crown size) [141][142][143]. The regular layout of roadside trees made the offset simple and spatially consistent [144,145], reducing the local registration noise for roadside trees.…”
Section: Matching Accuracy In Different Landscapesmentioning
confidence: 99%
“…Most roadside trees consist of broadleaved trees which were usually the same species, similar in tree age (i.e., tree height and crown size) [141][142][143]. The regular layout of roadside trees made the offset simple and spatially consistent [144,145], reducing the local registration noise for roadside trees.…”
Section: Matching Accuracy In Different Landscapesmentioning
confidence: 99%
“…But research revealed less than ideal situations. In different cities, transport land use had low tree biodiversity (Sever- Mutlu et al, 2017;Liu & Slik 2022;Źróbek-Sokolnik et al, 2021). Hong Kong shared a similar situation.…”
Section: Introductionmentioning
confidence: 99%